2022
DOI: 10.1371/journal.pone.0265719
|View full text |Cite
|
Sign up to set email alerts
|

Processing time affects sequential memory performance beginning at the level of visual encoding

Abstract: Electrophysiological studies have demonstrated that theta-band activity is useful for investigating neural mechanisms of memory. However, mechanisms specifically driving memory performance remain poorly understood. In sequential memory, performance can be artificially attenuated by shortening the inter-stimulus interval (ISI) between memory item presentations. Therefore, we sought to clarify the mechanisms of sequential memory performance by analyzing theta-band (4–8 Hz) activity recorded via magnetoencephalog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The authors concluded that alpha activity in sensory areas reflects storage buffers ( Kawasaki et al, 2010 ). In recent studies, during encoding, increases in theta activity in occipito-parietal regions have been commonly observed, and have been shown to reflect sensory processing of visual information and attention to visual stimuli ( Dugué et al, 2015 ; Pisella, 2017 ; Takase et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that alpha activity in sensory areas reflects storage buffers ( Kawasaki et al, 2010 ). In recent studies, during encoding, increases in theta activity in occipito-parietal regions have been commonly observed, and have been shown to reflect sensory processing of visual information and attention to visual stimuli ( Dugué et al, 2015 ; Pisella, 2017 ; Takase et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In each recording, the helmet-shaped sensor-array was tilted forward 10°. Three head position indicator coils were attached at subjects’ left and right pre-auricular points and nasion, and the head points were obtained using a digitizer according to standard MEG operating procedure ( Takase et al, 2022 ). Each subject was seated in the MEG measurement chair, onto which a table was attached.…”
Section: Methodsmentioning
confidence: 99%
“…The MEG recording procedure was approved by the Faculty of Health Sciences, Hokkaido University (Approval No. [21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Written informed consent was obtained from all participants prior to the experiments.…”
Section: Participants and Devicesmentioning
confidence: 99%
“…We have previously investigated amplitude modulation of alpha- [15,16] and theta- [30] rhythms during the performance of similar or identical sequential memory tasks. One of our previous works [16], in which 20 healthy older persons participated, revealed relationships between alpha-rhythm amplitude, memory performance, and scores indicative of possible mild cognitive impairment (MCI).…”
Section: Introductionmentioning
confidence: 99%